Farmland, Farm Credit and Agricultural Output Growth in Kano State, Nigeria: the Moderating Role of Murabahah Finance as a Proposed Framework - Bashir B.Aziz, Ahmad; Ibrahim Mohammed, Ahmed (International Journal of Engineering and Technology, 2018)
The objective of this paper is to propose a model to examine the moderating role of Murabahah finance on farmland, farm credit and agricultural output. Since, agriculture is the science and act of soil utilization, animals and forestry management in respect of food and raw materials for human satisfaction as well as poverty control and economic growth. On the other hand, the Kano state agricultural output is declining all with the socio-economic role of the output in the state economy. This paper proposes a model consider to be used by the ministry of agriculture and financial institutions in Kano state, Nigeria in order to overcome such issues. In addition, this paper introduces Murabahah finance as a new variable into the model and potential moderating variable. Also, this paper used a conceptual methodological approach.Â Â